Review of the Pathogenic Mechanism of Grape Downy Mildew (Plasmopara viticola) and Strategies for Its Control - Zhichao Zhang; Zaozhu Niu; Zhan Chen; Yanzhuo Zhao; Lili Yang (Microorganisms)
Downy mildew is among the most destructive diseases affecting grape production worldwide. It severely restricts the advancement of the grape industry. The causative pathogen, Plasmopara viticola, is an obligate biotrophic oomycete. Since the disease was introduced to Europe via grape cuttings in the 1870s, downy mildew has spread globally, resulting in devastating economic consequences. We review the current knowledge on the causative agent of grape downy mildew, its pathogenic mechanism, and control measures. Finally, we provide recommendations for developing more cost-effective strategies involving resistance genes and biocontrol agents to control grape downy mildew.